Augmenting Senior Secondary ESL Learners’ Reading Skills Through Explicit Instruction of Metacognitive Strategies - Al Ryanne Gabonada Gatcho; Bonjovi Hassan Hajan (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2019)
Reading and comprehending a text or selection in a language that is different from one’s native tongue can be a daunting task to many English as a Second Language (ESL) learners due to several reasons. Hence, teachers’ instructional strategies play a pivotal role in developing students’ reading skills. This study used a quasi-experimental design to discover the effects of using explicit or direct teaching of metacognitive strategies on the reading skills of students—comprehension skills and vocabulary. Forty grade 11 ESL students from a Chinese–Filipino school in Manila were selected through convenience sampling to be participants of the study. The performance of the two groups in comprehension and vocabulary was compared through pre-test and post-test. Using two-tailed t-test of dependent means, the significant difference between students’ performance in the reading comprehension test and the vocabulary test after the intervention was determined. Based on the results, there is no question that one’s comprehension and vocabulary size could be improved using explicit teaching of metacognitive strategies. The study has practical implications to the teaching of reading among ESL learners. Recommendations for future research are also provided in this paper.